Exploring positive teacher-student relationships: the synergy of teacher mindfulness and emotional intelligence - Wang, Xue (Frontiers in Psychology, 2023)
Introduction This study delves into the intricate synergy between teacher mindfulness and the quality of teacher-student relationships, with a specific and deliberate focus on the mediating influence of emotional intelligence. The way teachers engage with their students not only impacts the learning outcomes but also contributes significantly to the overall classroom atmosphere. Understanding the underlying mechanisms that drive these relationships is crucial for educators and policymakers alike. This research seeks to shed light on these critical dynamics. Methods To investigate this multifaceted interplay, a participant pool of 369 Chinese English teachers was assembled. The research employed a comprehensive approach to data collection, utilizing self-report questionnaires completed by the instructors. Structural equation modeling, a robust statistical technique, was employed to rigorously analyze the collected data. Results The data analysis unveiled a robust and direct association between teacher mindfulness and the quality of teacher-student relationships. Beyond this primary link, a noteworthy revelation emerged: emotional intelligence, as measured through our analysis, was identified as a pivotal mediating factor in this relationship. This finding highlights the intricate web of emotions, awareness, and interpersonal interactions that underpin effective teaching and positive teacher-student relationships. Discussion These significant findings underscore the critical roles of teacher mindfulness and emotional intelligence in shaping the educational landscape. The implications of this study reach far beyond academia, extending to the development of tailored educational interventions and support strategies.